Overcoming cancer drug resistance: insights into Apoptotic pathway modulation by plant-based nanoparticle and natural products - Singh, Amit Kumar; Kushwaha, Prem Prakash; Singh, Ajaya Kumar; Pandey, Abhay K. (Frontiers in Oncology, 2025)
Cancer is a complex progressive disease, characterized by uncontrolled cell growth, posing a serious global health problem across the population. The traditional treatments for this disease include chemotherapy, surgery, and radiation therapy, forming the backbone of care. However, over time, tumor cells often develop resistance to these treatments, making drug resistance a leading factor in disease progression and poor clinical outcomes for some patients. Cancer drug resistance is multifaceted at both the molecular and cellular levels. An important mechanism through which cancer cells acquire resistance to multiple drugs is dysregulated apoptosis (programmed cell death). This compromised apoptotic pathway resulted in prolongs cancer cell survival, accumulation of mutations that promote angiogenesis, stimulation of cell proliferation, impaired differentiation, and enhanced invasiveness during tumor progression. In the past few years, plant-derived natural products have garnered attention as promising therapeutic agents against drug-resistant cancers due to their minimal side effects and potent anticancer properties. However, their clinical application faces several challenges, including poor solubility, limited absorption, restricted tissue distribution, and rapid metabolism. An effective approach to address these limitations involves utilizing nanoparticles and nanomaterials, which can improve pharmacokinetics, enhance tumor-specific targeting, minimize side effects, and overcome drug resistance. This review delves into the fundamental molecular pathways associated with apoptosis and explores how phytochemicals and plant extracts, in combination with conventional drugs and plant-based nanoparticles can be utilized to treat cancer as well as cancer drug resistance by modulating its programmed cell death network.